RNAiAtlas: a database for RNAi (siRNA) libraries and their specificity - Mazur, Slawomir; Csúcs, Gábor; Kozak, Karol (Database, 2012)
Abstract. Large-scale RNA interference (RNAi) experiments, especially the ones based on short-interfering RNA (siRNA) technology became increasingly popular ov